Thoracophagus conjoint twin in Orang Asli – HTAA Experience - Abdullah, Suhaiza; R, Anna Liza; Abd. Aziz, Azian; Chin, Choy Nyok (2010)
Madam S, 21 year old Orang Asli , G2P1 was referred to ultrasound clinic at 17 weeks period of amenorrhea to determine the chorionicity. No history of multiple pregnancy in both couples and no family history of congenital anomaly. Clinical examination - fundal height corresponds to 18 weeks size. Detailed US - showed conjoint twins with the fetuses conjoined at the thorax & abdomen to the supraumbilical region (Figures2,3)). The fetuses share one heart. The liver appear fused. No other structural abnormality was noted. Parents were informed regarding guarded prognosis of the fetuses in view of the conjoined organs and risk of the fetuses being inseparable due to sharing of the heart. They opted for continuation of pregnancy. Fetal MRI at 32 weeks gestation - refer Figures 4&5 An elective caesarian section was planned but she had premature labour and emergency caesarean section was done. The baby girls was delivered with a combined weight of 3.3kg. Apgar Score was 81 and 95. As detected antenatal, the babies was fused from thorax to umbilicus (Figure 6). Echocardiogram show similar findings with fetal MRI. Unfortunately the babies expired at D5 post delivery due to complicated heart failure.